2013 3rd International Electric Drives Production Conference (EDPC) 2013
DOI: 10.1109/edpc.2013.6689720
|View full text |Cite
|
Sign up to set email alerts
|

Iron loss modelling which includes the impact of punching, applied to high-efficiency induction machines

Abstract: Within the market evolution towards higher efficiency machines, there is a need for more precise modelling tools, taking also higher frequency power supplies into account. This paper implements the effect of cut edge degradation, due to punching, on the local magnetization curve and local losses, aiming at improved calculation of magnetization current and machine iron losses. For an induction machine, defined by Leroy Somer and a high efficiency electrical steel, selected from ArcelorMittal's range, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 18 publications
0
39
0
1
Order By: Relevance
“…These elements are especially beneficial when we have to model a specific phenomenon in certain part of the solution domain efficiently. The developed loss model related to cutting presents a high degree of variation in permeability near the cut edge, which is normally represented by parabolic or exponential functions [6], [7]. However, it is observed that the cutting effect is negligible after 5-10 mm distance from the cut-edge.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…These elements are especially beneficial when we have to model a specific phenomenon in certain part of the solution domain efficiently. The developed loss model related to cutting presents a high degree of variation in permeability near the cut edge, which is normally represented by parabolic or exponential functions [6], [7]. However, it is observed that the cutting effect is negligible after 5-10 mm distance from the cut-edge.…”
Section: Introductionmentioning
confidence: 99%
“…5a , 6a and, 7a. Further, it should be noted that in general 4-5 different material layers of 0.5 mm-1 mm width of first order elements are normally introduced near the cut-edge [4], [6], [7]. Therefore, the first order reference mesh presented here can be treated as a reasonable mesh to model the presented cutting effect.…”
Section: B Accuracy Of Mixed Order Elementsmentioning
confidence: 99%
See 3 more Smart Citations